2016
DOI: 10.1108/he-05-2014-0068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dutch Skills for Life program on the health behavior, bullying, and suicidal ideation of secondary school students

Abstract: Purpose – The purpose of this paper is to evaluate the effects of the Dutch “Skills for Life” programme on students’ health behaviours, bullying behaviour and suicidal ideation. Design/methodology/approach – The effectiveness of the “Skills for Life” programme on health behaviour outcomes was evaluated at three points in time in using a cluster randomized controlled study design with a follow-up of 20 months. In total, 27 schools and 1,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 19 publications
(17 reference statements)
2
24
0
3
Order By: Relevance
“…Among programs that aim to increase skill-building, training delivery modality varies widely. Some programs like Skills for Life (Fekkes et al, 2016 ) and Relationships to Grow (Guarini et al, 2019 ) use tools such as role-play exercises, video and live demonstrative modeling, vignette discussion, and feedback embedded in a greater curriculum. NoTrap!…”
Section: Resultsmentioning
confidence: 99%
“…Among programs that aim to increase skill-building, training delivery modality varies widely. Some programs like Skills for Life (Fekkes et al, 2016 ) and Relationships to Grow (Guarini et al, 2019 ) use tools such as role-play exercises, video and live demonstrative modeling, vignette discussion, and feedback embedded in a greater curriculum. NoTrap!…”
Section: Resultsmentioning
confidence: 99%
“…The program is based on social learning theory and Rational Emotive Behavioral Therapy. As a result, the program aims to reduce bullying by enabling students to learn from each other in a classroom setting through behavioral modeling.The program is implemented by teachers, who attend two 3-day training workshops prior to implementation and receive "booster" training sessions throughout the intervention(Fekkes et al, 2016).The intervention is comprised of 25 lessons that are delivered over the course of two academic years. First, four lessons address awareness and handling of thoughts and feelings.…”
mentioning
confidence: 99%
“…In the Take the Lead programme examined by Domino (2013), teachers were trained by external trainers for a minimum of six hours to deliver a curriculum designed to enhance students' social learning during regular class periods. Fekkes et al (2016) also found teachers were extensively trained in the principles and ideas of the Skills for Life curriculum to deliver 25 lessons over two school years.…”
Section: Standalonementioning
confidence: 99%
“…In line with this, several studies emphasise teacher training (Cross et al, 2018;Haataja et al, 2014;Wurf, 2012), for example Haataja et al (2014, p. 567) who describe a two-day pre-implementation training programme for teachers responsible for delivering lessons or for managing acute cases of bullying. Concern for curriculum delivery was also evident in the emphasis on implementation manuals (Battey & Ebbeck, 2013;Bonell et al, 2018;Domino, 2013;Fekkes et al, 2016), as demonstrated by (Cross et al, 2018) who described a six-hour group training session for pastoral care staff complemented by "a manual to guide whole-school implementation" (p. 501).…”
Section: Gaps In Understanding Of Curriculum Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation